Supply, installation, commissioning and post implementation support of structured cabling and passive network with manufacturer's 25 years site certification for Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Optimal Technology (Pvt.) Ltd. to supply, installation, commissioning and post implementation support of structured cabling and passive network with manufacturer's 25 years site certification for the Brac University new campus project.